PERCEPTUAL ANALYSIS OF ETHICAL FACEBOOK MARKETING - Sharma, Ritika (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2023)
The primarily motive is to investigate the Ethical concern of customers towards the Facebook Marketing. The various past studies explored the benefits of Online Marketing and Facebook is a very popular Social platform among it and in the transforming world so far. Most of the research work was done on describing the security concerns as well as perception of customer towards S-commerce but yet not discovered the ethical values towards Facebook Marketing and what customers actually feel about Facebook Marketing. Due to time constraints, snowball sampling was used to collect the data from the respondents and only 250 respondents were selected for the study, those who were frequently accessing the Facebook and other social platforms for shopping purposes. Prior to actual research, pilot survey was conducted to ensure that all the questions were asked in questionnaire were understandable as well as appropriate for this study. In addition, Cronbach’s Alpha techniques were used to check whether all statements have positively correlated to each other. Therefore, reliability of the statements extracted which allowed us to proceed further for analysis of the data. In this study, three factors were extracted through factor analysis, from the responses of respondents. Based on the variables included in each factor, we labeled for factors as quality services, mechanisms of trust, adoption of Facebook Marketing, prosperity of shopping, flexibility behavior and user friendly. The findings of the study highlighted the importance of quality services offered by the E-Marketers. The websites marketers must be user-friendly so that consumers feel flexible or free to make purchases at low prices. The marketers should be focused on the youth, because youth generation is very much prosperous regarding online shopping, because Facebook Marketing provides varieties of products, lower shipping fee, easily accessibility of products and provide products to their home. There are many laws and acts which increases trust among customers regarding the Facebook Marketing. The privacy of customers is also a concern, their personal information would not be shared with others or third party and proper feedback is provided to the customers regularly.